Bibliometric analysis combined with visualization on universal trends and hot topics of LOX family in human diseases: 1995 to 2025 - Yang, Tingting; Li, Heng; Zhou, Wenxuan; Zhang, Ning; Tian, Zhenyu; Wang, Heming; Feng, Yuyan; Chen, Yunguang; Wang, Zhen (Frontiers in Oncology, 2025)
IntroductionLysyl oxidase (LOX) is crucial for modifying collagen and elastin, thereby preserving tissue integrity. Aberrant LOX activity has been associated with a multitude of health disorders, including cutaneous, pulmonary, fibrotic, cardiovascular diseases, and cancer. In cancer, LOX can either promote or inhibit tumor development, and its expression level is closely correlated with patient prognosis.MethodsThis research utilized data retrieved from the Web of Science Core Collection on May 30, 2025. The search strategies were crafted to target LOX – related terms while excluding irrelevant ones, and the data were limited to English – language articles. Over the past 30 years, 9261 LOX – related publications were identified. The number of articles exhibited an upward trend, especially in the past decade. The United States, China, and Japan were the leading countries in terms of publication output, with institutions like Harvard University and Boston University being highly productive.ResultsThis research utilized data retrieved from the Web of Science Core Collection on May 30, 2025. The search strategies were crafted to target LOX – related terms while excluding irrelevant ones, and the data were limited to English – language articles. Over the past 30 years, 9261 LOX – related publications were identified. The number of articles exhibited an upward trend, especially in the past decade. The United States, China, and Japan were the leading countries in terms of publication output, with institutions like Harvard University and Boston University being highly productive.DiscussionThis study presents an overview of LOX - related research. Comprehending the mechanisms of LOX can offer valuable perspectives on tumor biology. Future research on LOX – extracellular matrix interactions and associated gene pathways may lead to the development of novel diagnostic and treatment modalities targeting LOX.